2021
DOI: 10.2147/ppa.s310689
|View full text |Cite|
|
Sign up to set email alerts
|

Potential Development of a Mobile Application for Gout Self-Management: What Support Do Patients Need?

Abstract: Purpose With the increasing prevalence and chronic course of gout, the use of mobile health (mHealth) applications (APPs) for gout self-management is attracting considerable research attention as an effective approach to improving health outcomes. However, there is limited knowledge regarding the self-management support that a mHealth APP for gout should provide to patients according to their needs. The aim of this study was to interview patients with gout and identify their needs with respect to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Health education is a crucial intervention method for continuous care and a primary means to promote chronic disease self-management. In our previous studies, we identified the health education needs of patients with gout through qualitative interviews [ 27 ]. Next, we used this information to develop an mHealth-based gout continuous care program.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Health education is a crucial intervention method for continuous care and a primary means to promote chronic disease self-management. In our previous studies, we identified the health education needs of patients with gout through qualitative interviews [ 27 ]. Next, we used this information to develop an mHealth-based gout continuous care program.…”
Section: Discussionmentioning
confidence: 99%
“…In China, the mHealth support necessary for the self-management of patients with gout includes instrumental support (health education, hospital registration, setting reminders, and shopping), relational support (interactions with health care providers and fellow patients), and psychological support (helping patients mitigate various negative emotions) [ 27 ]. Using the IFSMT, we developed the Gout Intelligent Management app, an mHealth app for continuous gout care.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with gout usually suffer from pain, joint deformity, impaired mobility, kidney damage, anxiety, depression, and other problems, which seriously jeopardize the physical and mental health and quality of life of patients with gout [ 3 , 4 ]. As a chronic disease, gout is prone to recurrent flares (when symptoms get worse), and patients with gout need to take action to manage the disease over the long term to improve their health outcomes [ 5 ]. However, the current health behaviors and health outcomes of patients with gout need to be improved.…”
Section: Introductionmentioning
confidence: 99%